The Delusional Addiction & Ignorance Associated with Fitness Regimes - Thomson, Wendy (British Journal of Healthcare and Medical Research, 2025)
This article explores the risks of exercise regimes that, while intended to promote health, may instead cause physical and psychological harm. Both the public and professional athletes are vulnerable—athletes face intense pressure to adhere to extremely demanding training programs, often under the influence of under-qualified trainers, resulting in excessive injury, career-ending conditions, or even suicide.